A frequent pattern mining algorithm based on FP-growth without generating tree - Tohidi, Hossein; Ibrahim, Hamidah (Universiti Utara Malaysia, 2010)
An interesting method to frequent pattern mining without generating candidate pattern is called frequent-pattern growth, or simply FP-growth, which adopts a divide-and-conquer strategy as follows. First, it compresses the database representing frequent items into a frequent-pattern tree, or FPtree, which retains the itemset association information. It then divides the compressed database into a set of conditional databases (a special kind of projected database), each associated with one frequent item or pattern fragment, and mines each such database separately. For a large database, constructing a large tree in the memory is a time consuming task and increase the time of execution. In this paper we introduce an algorithm to generate frequent patterns without generating a tree and therefore improve the time complexity and memory complexity as well. Our algorithm works based on prime factorization, and is called Frequent Pattern-Prime Factorization (FPPF).